The Effect of Profitability Ratio to the Share Price of Listed Lq 45 Index State-Owned Companies on The Indonesia Stock Exchange - Sari, Maya Macia (Journal of Community Research and Service, 2022)
This study was conducted to find out how the effect of Retun on Assets (ROA), Net Profit Margin (NPM), Return on Equity (ROE) and Earning Per Share (EPS) on Stock Price in state-owned enterprises  LQ 45 Index listed on the Indonesia Stock Exchange. The data is taken from the official website of the Indonesia Stock Exchange, namely www.idx.co.id.  The data used for the period 2017 to 2020. The population in this study was 18 companies with a sample of 12 companies used. This study used quantitative data processed with the Eviews v. 12 Application, with a panel data regression analysis  method. The test results showed that thevariables Return on Assets (ROA), Net Profit Margin (NPM), Return on Equity (ROE) and Earning Per Share (EPS) had  a positive and significant effect on Harga Saham.  Thevariables Rorrn on Assets (ROA), Net Profit Margin (NPM), Return on Equity (ROE) and Earning Per Share (EPS have  a positive and significant effect on Harga Saham.  The contribution of influence given by the entire variable was 81.01%.